2021
DOI: 10.1111/bjso.12471
|View full text |Cite
|
Sign up to set email alerts
|

Video games, frustration, violence, and virtual reality: Two studies

Abstract: The degree to which the content of video games influences aggression continues to be debated in the scholarly literature. The current article includes two studies, one of which replicates one study from Przybylski et al. (2014, J. Pers. Soc. Psychol., 106, 441) and the other which extends related concepts into virtual reality. In the first study, two versions of Tetris were examined, differing in levels of difficulty. In the second study, participants played virtual reality games which differed in regard to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…This has been confirmed in some studies that have found a correlation with violent gameplay and cognitive aggression, particularly in an environment with greater presence or immersion (American Psychological Association [APA], 2020; Anderson et al, 2010;Lull & Bushman, 2016). On the other hand, other studies show that the link between violent VR video games and aggression (cognition and behavior) is inconclusive (Drummond et al, 2021;Ferguson et al, 2021). However, as Haam and Spaaj (2015) have determined, the pathway to violent extremism is multifaceted, and it involves conveying personal and political grievances to supportive online networks and being enabled by charismatic extremists; therefore, these studies may not be viable in the context of the metaverse and its features.…”
Section: Figurementioning
confidence: 70%
“…This has been confirmed in some studies that have found a correlation with violent gameplay and cognitive aggression, particularly in an environment with greater presence or immersion (American Psychological Association [APA], 2020; Anderson et al, 2010;Lull & Bushman, 2016). On the other hand, other studies show that the link between violent VR video games and aggression (cognition and behavior) is inconclusive (Drummond et al, 2021;Ferguson et al, 2021). However, as Haam and Spaaj (2015) have determined, the pathway to violent extremism is multifaceted, and it involves conveying personal and political grievances to supportive online networks and being enabled by charismatic extremists; therefore, these studies may not be viable in the context of the metaverse and its features.…”
Section: Figurementioning
confidence: 70%
“…More subsectors will probably emerge from this sector, but others will also start to use its knowledge more widely. The recent years (2020-2022) of the COVID-19 pandemic and the hybrid wars have meant that solutions are already being implemented more widely: the use of games in education processes (Haberlin and Atkin, 2022), the possibilities of new areas of behaviour analysis (Ferguson et al, 2022;Scolari, Pires, andMasanet, 2022), reality andvirtual design (Reer, Wehden, Janzik, Tang, andQuandt, 2022), development of cybersecurity (Khan, Merabet, Alkaabi, and El-Sayed, 2022), and others. Research on the directions of diffusion of knowledge from this sector is indeed the future of many areas of science.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…El fenómeno de los videojuegos es objeto de debate actual en la literatura académica (Ferguson, 2020;Ferguson et al, 2021). Investigaciones efectuadas a inicios del nuevo milenio han contemplado que el contenido y jugabilidad de los primeros videojuegos promovían estereotipos sociales y poseían cierta tendencia hacia la violencia.…”
Section: Introductionunclassified